The Role of Osing Women in Preserving Banyuwangi Customs and Culture - Maulana, Rizky (CV. Sekawan Siji, 2024)
Osing women are a group of women who are able to participate in various cultural activities. They contribute significantly to the preservation and transmission of their cultural traditions to future generations through their traditional clothing. The distinctive aspects of their lives will be examined in this paragraph, along with their traditions, beliefs, and contributions to Indonesian society. The articles mentioned discuss how gender equality can affect the preservation of cultural heritage and the role of women in the ikat weaving industry. Women's empowerment strategies through access to training, capital, and fair markets are needed to maintain traditional knowledge and promote ikat weaving as a valuable cultural asset. Women in Indonesia are addressing barriers to achieving their goals by supporting laws that promote justice and equal opportunity. It is imperative that we create spaces for women to share their stories and contribute to the ongoing conversation about gender equality and empowerment.